Diseño de un sistema de implantación de BPMS para la planta de faenamiento “Don Chachita” en el cantón Salcedo provincia de Cotopaxi. - León Chancusig, Klever Daniel (2020)
This qualification work consists of performing a good manufacturing practices system in the microenterprise "DON CHACHITA" located in the canton Salcedo province of Cotopaxi. For the development of research, the ARCSA-DE-067-2015-GGG Technical Standard substitute for processed foods (BPM) and product quality and safety assurance were taken as a baseline. Initially an internal audit was carried out to determine the current status of the micro-enterprise with respect to Good Manufacturing Practices, this audit consists of the application of a check list that includes all the requirements required by the regulations in force in Ecuador by which the violations of the following aspects are identified: Facilities, equipment and utensils, hygienic manufacturing requirements, raw materials and inputs, production operations, packaging, labelling and packaging, storage, distribution, transport and quality assurance. As the results of the initial audit, the following results were obtained, 52.11% compliant, 35.63% are not compliant and ultimately 15.15% do not apply.-with these results a gradual plan of implementation of the (BPM) was developed this plan is aimed at complying with the requirements of the regulations, for which standardized operating procedures (SOOs) were developed, according to the needs found for the implementation of the gradual plan, and so that the micro-enterprise can market safe products suitable for human consumption.